In Silico Evaluation of Cardiac Glycosides from Vernonia amygdalina as EGFR Inhibitors in Triple Negative Breast Cancer - Gisela Agustin Habayahan; Denny Satria (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
Triple-negative breast cancer (TNBC) is an aggressive subtype with limited targeted therapies, emphasizing the urgent need for novel molecular inhibitors. Epidermal growth factor receptor (EGFR) is overexpressed in TNBC, but current inhibitors show limited clinical efficacy, indicating a significant therapeutic gap. This study aims to evaluate cardiac glycosides from Vernonia amygdalina as EGFR inhibitors using an integrated in silico approach. Docking results demonstrated that vernoniosides A3 exhibited the lowest binding energy of -12.2 kcal/mol, outperforming the native ligand (-9.0 kcal/mol) and gefitinib (-8.5 kcal/mol). Molecular dynamics (MD) simulations revealed that EGFR-vernoniosides A3 complex remained stable, with RMSD values within stable range (0.7-3.8 Å), RMSF values (0.4-8.3 Å), radius of gyration (Rg) (6.0-7.0 Å), solvent-accessible surface area (SASA) (830-871 Å²), while forming up to 15 hydrogen bonds. However, MM-PBSA analysis showed that binding free energy of vernoniosides A3 (321.60 ± 5084.43 kcal/mol) was lower than the native ligand (569.25 ± 8997.10 kcal/mol) and gefitinib (623.87 ± 9862.73 kcal/mol), indicating weaker thermodynamic binding strength. This discrepancy arises as docking measures potential binding in a static state, while MM-PBSA reflects dynamic, realistic binding strength. These results suggest that vernoniosides A3 shows promising binding affinity but requires further optimization and validation for TNBC therapy.